The Impact of Agricultural Mechanisation on Poverty Alleviation in a Seasonal Environment: a project evaluation from northern Bangladesh - Sebastian Zug (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2008)
Transformation processes in the mode of agricultural production can significantly influence both, the farmers' and the labourers' social welfare. Active promotion of new forms of agricultural production through Governments and NGOs has to be in line with their policies. In the example of Bangladesh poverty reduction is the principle concern of rural development policies. Hence, an ex-ante evaluation to determine an agricultural project's impact on the rural people's livelihoods is a central precondition prior to the implementation of such a project. In this working paper an agricultural pilot project was analysed, which is going to be implemented in a vast area of Northern Bangladesh. Through agricultural extension a short-duration paddy variety, early planting dates, and mechanization of the plantation process are being promoted. This allows harvest of paddy one month ahead of current practice. Major positive welfare changes can be expected for the farmers, especially since earlier plantation of subsequent crops leads to higher yields. The labourers' social welfare will be affected by two aspects. Since mechanization is labour displacing, the overall employment is expected to decrease. Secondly, a positive effect of the project is expected because of the high seasonality of employment opportunities in the region. Harvest will take place in the current agricultural lean season, which corresponds to the period of seasonal food crisis. Hence, harvest is shifted to that period, when labourers are most in need of it. The expected change in social welfare of the farmers and the labours was determined independently by applying cost benefit analysis. Farmers are expected to be the winners of the project, while the labourers' loss in seasonality cannot be compensated by the benefit from smoothened seasonality. The working paper will discuss in how far normative development objectives of the implementing organizations are in line with the reality of the project, which favours those considered being less poor (farmers) and disfavours those considered being more poor (labourers). Additionally, an alternative project idea will be analysed and discussed, which does not mechanize agriculture and therefore has a less widening effect on rural income distribution.
Keywords: 320; Bangladesh; Poverty alleviation; Agriculture; Ländliche Armut; Armutsbekämpfung; Agrartechnik; Saisonale Schwankungen; Projektbewertung; Wirkungsanalyse; Bangladesch